Strategi Implementasi Program CoE (Center of Excellence) pada Kompetensi Keahlian Teknik Instalasi Tenaga Listrik: (Studi Kasus di SMK Negeri 1 Kabupaten Jayapura) - Arika Arika; M. Syukri Nawir; A. Ubaidillah; Muhamad Yusuf; Zulihi Zulihi (Cetta: Jurnal Ilmu Pendidikan, 2023)
This research aims to learn about the Center of Excellence (CoE) Program Implementation Strategy on Electrical Power Installation and the factors that influence the Center of Excellence (CoE) program implementation strategy on electrical power installation engineering expertise competencies at SMK Negeri 1 Sentani. This type of research uses a qualitative approach, research data obtained through observation, interviews, and documentation, while data analysis techniques use a flow model, namely: data reduction, data display, coclusion drawing/verification.  Research results: SMK Negeri 1 Sentani has designed a strategy to achieve the success of the CoE program. First, develop a network with PT. PLN Sentani Branch and PT. Kabantaras officially through the signing of the MoU. Second, providing optimal services to students focused on curricular services (learning) Third, improve students' abilities by making improvements and developing learning input components. These three strategies support each other to achieve program success in stages. The factors that influence the implementation strategy of the Center of Excellence program are communication factors and resource factors, which are well established between the school, IDUKA instructors, and students, so that the implementation of the CoE program is guided by the strategy. The factors that influence them are capital, curriculum, and infrastructure with IDUKA standards.